THE INFLUENCE OF MOTORIC AND COGNITIVE ABILITIES ON THE SUCCESSFULNESS IN SITUATIONAL MOTORIC TESTS IN VOLLEYBALL - Bećir Šabotić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
The process of management of moving in volleyball is significally leaning on the activity of analyst. By practicing the game the sharpness of visual, tactical, cinestatical, vestbular and hearing feelings are significally improving. The aim of this work is to consolidate the relation between motoric and cognitive abilities of situational motoric abilities in volleyball. The sample of examination is taken from the population of pupils in eighth grade of primary school. For the processing of results the method of canonically - corelational analyses has been used. According to the given results it can be concluded that there is a very significant connection between the group of predictorical variables of motoric and cognitive abilities with the group of criteria variables of situational motoric abilities. Results like this are logical as well concerning the structure of performing the exercises in volleyball, which comes from the performing of quick movements and good coordination.